FUNCTIONAL SYNTAXEMIC STUDY OF INCOMPLETE SENTENCES IN DIALOGIC SPEECH (BASED ON ENGLISH AND UZBEK LANGUAGES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, functional syntaxemic features of incomplete sentences in dialogic speech based on English and Uzbek languages are studied. In addition, the article examines the analysis of the information structure of the dialogic text (speech), its connection with the communicative division.